(untitled) (Ecological Bulletin of Kryvyi Rih District, 2025)
Macrophytes have a wide range of ecological roles and make a significant contribution to the structure, viability and functioning of hydroecosystems, helping to maintain ecological balance, biodiversity and appropriate water quality. Aquatic plants are important components of biogeochemical cycles; they participate in nutrient cycling, gas exchange regulation and water purification. The root systems of aquatic plants help to stabilize the sediment and coastal soil, thereby reducing the risk of erosion and siltation of riverbed. Macrophytes are sensitive to changes in the physicochemical properties of water, such as the concentration of pollutants, oxygen content, temperature and water purity. Such bioindicative properties are used to monitor the ecological state of rivers and predict environmental changes. Fluctuations in the structure of macrophyte communities can indicate eutrophication of water bodies, their pollution with heavy metals or pesticides, disruption of the hydrological regime and degradation of the ecosystem as a whole. The paper considers the classification of aquatic plants taking into account different approaches; in more detail, with a large number of examples, by life form. Among the many functions of macrophytes in river ecosystems, the authors have more thoroughly examined the role of macrophytes in purifying water from pollutants. Eutrophication of water and pollution of water bodies with heavy metals are the result of anthropogenic activity, which threatens the people health, aquatic organisms and entire ecosystems. Traditional methods of water purification are mostly expensive, not always environmentally safe, inefficient and time-consuming. Phytoremediation is a modern technology for water purification using various types of macrophytes, which has gained popularity due to the discovery of plants capable of removing excessive concentrations of essential nutrients and/or accumulating heavy metals. The elimination of pollutants can occur by various mechanisms (phytoextraction, phytostimulation, phytostabilization, phytoevaporation, phytodegradation), but the main thing is the fact of removing a large number of pollutants, which leads to the purification of the water bodies. Phytoremediation is a relatively inexpensive biotechnology that has been rapidly developing recently. The paper analyzes studies on the ability of macrophytes to reduce N and P concentrations, with hydatophytes playing a particularly important role in this process, which are capable of enhanced absorption of nutrients by stems. The paper also analyzes studies of hydrophytes and hydatophytes for their ability to remove some heavy metals and metalloids (Zn, As, Cu, Cd, Cr, Pb and Hg), thereby contributing to the revitalization of polluted rivers and even technogenic reservoirs (such as tailings ponds). The latter is very relevant for solving the ecological problems of the hydroecosystem of the technogenically-loaded region of Kryvbas. It is shown that the most important part of active phytoremediation is the selection of effective plant species.